STRATEGY OF SUBMITTING JOURNAL INDEXATION TO SCOPUS: A STUDY ON ASEAN JOURNAL ON SCIENCE & TECHNOLOGY FOR DEVELOPMENT - Fauzi, Syahrul; Istiana, Purwani; Purwitorosari, Pradiastuti; Tri Utami, Agustina Asih; Winarsih, Winarsih; Gandawanti, Sasmita (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2025)
Journal indexing is a key indicator of scientific quality, enhancing the visibility, credibility, and dissemination of academic publications. This study presents a case analysis of the Asian Journal of Science and Technology Development (AJSTD) and its successful indexing in the Scopus database, offering strategic insights and potential best practices for other scholarly journals. Using a qualitative case study approach through observation and documentation, the findings reveal that AJSTD’s initial submission on 17 March 2020 was rejected by the Scopus Content Selection & Advisory Board (CSAB) due to several shortcomings. However, after a comprehensive revision based on reviewer feedback, the journal reapplied and was officially accepted on 17 October 2020. This process underscores the importance of meeting Scopus selection criteria, including content quality, citation performance, international diversity, and publishing ethics. Minor deficiencies, if left unaddressed, can become critical obstacles when combined with other weaknesses. AJSTD’s experience demonstrates that strategic editorial improvement, transparent communication, and a commitment to continuous quality enhancement can transform initial rejection into success. More importantly, this study contributes a practical framework that can serve as a reference or model for journals, particularly those from developing countries, seeking international recognition through global indexing. The lessons drawn from AJSTD’s experience are expected to guide journal managers and editorial teams in navigating the complex and competitive landscape of academic indexing more effectively.